PENGEMBANGAN Nitzschia sp. SEBAGAI BIOTA UJI SEDIMEN - Rachma Puspitasari (Pusat Penelitian Oseanografi LIPI, 2019)
DEVELOPMENT of Nitzschia sp. AS SEDIMENT TEST ORGANISM. Sediment bioassay requires a test organism which suitable with the test material, for example sediment. However, benthic phytoplankton as the test organism has not been widely applied in Indonesia. Recently, bioassay test still uses phytoplankton which lives in water column such as Chaetoceros gracilis, Tetraselmis sp., Isochrysis sp., or uses another test organism like mussel, sea urchin larvae and amphipod. In addition, Nitszchia sp. is one of culture collection at Research Centre for Oceanography so it could be added value of culture collection. Therefore, this paper aims to describe the potential use of phytoplankton benthic, Nitzschia sp. as sediment test organism.